The Obsessive Behaviors in Jade Halley Bartlett’s Miller’s Girl (2024): A Psychoanalytic Perspective (PANOPTICON: Journal of English Studies, 2025)
This study examines the portrayal of obsessive behavior in Jade Halley Bartlett’s Miller’s Girl (2024), focusing on the psychological dynamics between the two central characters, Cairo and Mr. Miller. The research investigates how emotional factors such as loneliness, unmet psychological needs, and emotional neglect shape the characters’ mental states and contribute to the development of obsessive attachments. Grounded in Sigmund Freud’s psychoanalytic theory, this study employs a qualitative descriptive method, analyzing selected scenes and dialogues that illustrate patterns of obsession and psychological disturbance. The findings indicate that Cairo’s obsession emerges from parental absence and her intense need for validation, whereas Mr. Miller’s fixation is rooted in emotional rejection within his marriage and his desire to regain a sense of worth through Cairo’s admiration. Both characters rely on rationalization as a defense mechanism, though they employ it in markedly different ways to justify or manage their behaviors. This study highlights how obsessive tendencies are constructed within cinematic narratives and contributes to literary psychology research by demonstrating the relevance of psychoanalytic theory in interpreting contemporary film portrayals of mental and emotional instability